Diagnostic accuracy for self‐reported methamphetamine use versus oral fluid test as the reference standard in a methamphetamine‐dependent intervention trial population. (3rd December 2022) - Carter, Gregory; Spittal, Matthew J.; Glowacki, Linda; Gerostamoulos, Dimitri; Dietze, Paul; Sinclair, Barbara; Arunogiri, Shalini; Berk, Michael; Lubman, Dan I.; Manning, Victoria; Higgs, Peter; Quinn, Brendan; et al.
Abstract: Aims: Treatment of methamphetamine dependence requires monitoring of recent use or abstinence. Self‐report is commonly used for routine monitoring, but the accuracy of self‐report is not established. For the treating clinician, the key accuracy statistic is the negative predictive value (NPV). The study aim was to estimate the NPV of self‐reported non‐use of methamphetamine compared with an oral fluid reference standard. Design, Setting and Participants: This study was a secondary (subgroup) analysis from a randomized controlled pharmacotherapy trial. Three Australian outpatient addiction services took part. Particpants were 139 people dependent on methamphetamine. Measurements: Weekly oral fluid samples over 12 weeks to determine methamphetamine (and amphetamine) concentrations were used as the reference standard. Self‐report of any methamphetamine use in the previous 7 days by the time‐line follow‐back method was the index test. Standard diagnostic accuracy statistics were calculated for all available paired episodes ( n = 1134). Three NPV values were calculated: unadjusted NPV and NPV adjusted for clustering of observations through logistic regression and generalized estimating equation (GEE). We also calculated the NPVs for a range of prevalence rates of methamphetamine use, for the calculated levels of sensitivity and specificity. Findings: Sensitivity was 96.4% [95% confidence interval (CI) = 95–97.5], specificity was 63.7% (95% CI = 57.3–69.8) and positive predictive value (PPV) was 90.8% (95% CI = 88.8–92.6). The unadjusted NPV was 82.7% (95% CI = 76.5–87.9), adjusted NPV by logistic regression 82.7% (95% CI = 73.9–91.5) and GEE 76.8% (95% CI = 66.8–86.8). At a methamphetamine use prevalence of 5%, the estimated NPV would be 99.7% (95% CI = 99.6–99.9) and at 95% prevalence, 48.2% (95% CI = 39.6–57.0). Conclusions: Self‐report of no recent methamphetamine use appears to be sufficiently accurate to be clinically useful at the expected prevalence rates of methamphetamine use in clinical treatment settings. If generalizable to clinical settings, where these tests are routinely conducted, this may permit a reduction in the frequency and cost of oral fluid assays.